Technology development for Army unmanned ground vehicles (National Academies Press, 2002)
Unmanned ground vehicles (UGV) are expected to play a key role in the Army's Objective Force structure. These UGVs would be used for weapons platforms, logistics carriers, and reconnaissance, and surveillance among other things. This report discusses UGV operational requirements, development efforts, and technology integration and roadmaps.